Standardization of the FAO/IAEA Flight Test for Quality Control of Sterile Mosquitoes - Maïga, Hamidou; Lu, Deng; Mamai, Wadaka; Bimbilé Somda, Nanwintoum Séverin; Wallner, Thomas; Bakhoum, Mame Thierno; Bueno Masso, Odet; Martina, Claudia; Kotla, Simran Singh; Yamada, Hanano; Salvador Herranz, Gustavo; Argiles Herrero, Rafael; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Successful implementation of the Sterile Insect Technique (SIT) against Aedes aegypti and Aedes albopictus relies on maintaining a consistent release of high-quality sterile males. Affordable, rapid, practical quality control tools based on the male’s flight ability (ability to escape from a flight device) may contribute to meet this requirement. This study therefore aimed to standardize the use of the original FAO/IAEA rapid quality control flight test device (FTD) (version 1.0), while also improving handling conditions and reducing the device’s overall cost by assessing factors that could impact the subsequent flight ability of Aedes mosquitoes. The new FTD (version 1.1) is easier to use. The most important factors affecting escape rates were found to be tube color (or ‘shade’), the combined use of a lure and fan, mosquito species, and mosquito age and density (25; 50; 75; 100 males). Other factors measured but found to be less important were the duration of the test (30, 60, 90, 120 mins), fan speed (normal 3000 rpm vs high 6000 rpm), and mosquito strain origin. In addition, a cheaper version of the FTD (version 2.0) that holds eight individual tubes instead of 40 was designed and successfully validated against the new FTD (version 1.1). It was sensitive enough to distinguish between the effects of cold stress and high irradiation dose. The eight-tube FTD may therefore be used to assess Aedes flight ability. This study demonstrated that the new designs (versions 1.1 and 2.0) of the FTD could be used for standard routine quality assessments of Aedes mosquitoes required for an SIT and other male release-based programmes.